Composing functions means that the input of the outer functions is the output of the inner function.
In fact, you can rewrite the circle notation as
![(f\circ g)(x)=f(g(x)),\quad (g\circ f)(x)=g(f(x))](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%28x%29%3Df%28g%28x%29%29%2C%5Cquad%20%28g%5Ccirc%20f%29%28x%29%3Dg%28f%28x%29%29)
So, we can substitute g(x) with its expression:
![(f\circ g)(x)=f(g(x))=f(4x+2)](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%28x%29%3Df%28g%28x%29%29%3Df%284x%2B2%29)
And since f(x)=x+5, we simply have to add 5 to its input:
![f(4x+2)=(4x+2)+5=4x+7](https://tex.z-dn.net/?f=f%284x%2B2%29%3D%284x%2B2%29%2B5%3D4x%2B7)
Similarly, we have, substituting f with its expression,
![(g\circ f)(x)=g(f(x))=g(x+5)](https://tex.z-dn.net/?f=%28g%5Ccirc%20f%29%28x%29%3Dg%28f%28x%29%29%3Dg%28x%2B5%29)
And since g(x)=4x+2, we have to multiply the input by 4 and add 2:
![g(x+5)=4(x+5)+2=4x+20+2=4x+22](https://tex.z-dn.net/?f=g%28x%2B5%29%3D4%28x%2B5%29%2B2%3D4x%2B20%2B2%3D4x%2B22)
-3x - 3.2 no
-1.2-8 no
-1.2x-3.2 yes
-1.2x+3.2 no
Answer is 60 U need to calculate carefully with brackets involving multiplication